Awareness on prohibited elements in Muamalat: common practice in life / Wan Musyirah Wan Ismail, Ida Rahayu Mahat and Nurul Asma Mazlan - Wan Ismail, Wan Musyirah; Mahat, Ida Rahayu; Mazlan, Nurul Asma (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
Muamalat in Islam literally means transaction and technically means any mutual dealing that exist between two parties in order to solve their everyday needs, normally in trade and commerce. In Islamic economy, it is based on fiqh al-muamalat, which regulates the trading and commercial activities. There are three prohibited elements in transaction namely riba (interest), gharar (uncertainty), and maysir (gambling). However, certain Muslim community are still practising the trading that consist of these elements. An existence of many Islamic banks in Malaysia since 1983, however, seems unable to eliminate these elements in the Muslim's daily life. Therefore, this paper aims to examine the awareness of the public regarding the practice of these three prohibited elements in their daily life. This study used quantitative method and employed descriptive studies. 150 questionnaires were distributed to the public using simple random sampling. Results found that there are lack of awareness of respondents regarding common activities in our daily life that contains prohibited elements. It is recommended to give more knowledge regarding prohibited elements to the Muslims through social media.